What Combination of Generic Bedside Screening Tools Is Optimal to Capture Patients with Penetration/Aspiration Due to Dysphagia? Comparing Single Bedside Tools Versus Combinations of Tools for Sensitivity and Specificity - Albert Westergren; David Smithard; Johannes Riis; Christina Emborg; Anne Lund Krarup; Dorte Melgaard (Geriatrics)
Background/Objectives: This study aimed to explore the validity of various generic bedside screening tools, and combinations of these, for capturing dysphagia as compared to aspiration/penetration found through the Flexible Endoscopic Evaluation of Swallowing (FEES). Methods: In this cross-sectional study, participants diagnosed with chronic pulmonary disease (n = 25), Parkinson’s disease (n = 26), multiple sclerosis (n = 24), or stroke (n = 25) participated. Patient-reported outcomes and clinical-rated assessments included: the four-question test (4QT), the Minimal Eating Observation Form—II, the Volume–Viscosity Swallow Test (V-VST), the Penetration–Aspiration Scale, and the FEES. Activities in daily living were assessed with the Barthel Index. The sensitivity, specificity, negative predictive value (NPV), positive predictive value, and accuracy were calculated. Results: The 100 participants’ median age was 72 years, and 42 were women. In total, 78 patients had eating difficulties (MEOF-II). According to the 4QT, 69 patients had dysphagia while 62 had it according to the V-VST. Furthermore, 29 patients had penetration/aspiration according to the FEES. All generic bedside tools performed better when combined with another tool, when compared to the identification of penetration/aspiration according to the FEES. The combination of the MEOF-II and 4QT as well as the combination of the MEOF-II and V-VST proved to have very high sensitivity (96.1–96.3%) and NPVs (92.3% in both instances). Combining the three tools, the MEOF-II, 4QT, and V-VST, did not improve the sensitivity or NPV. Conclusions: A combination of the MEOF-II and 4QT or the MEOF-II and V-VST bedside tools is recommended for identifying patients at risk of penetration/aspiration and in need of further in-depth clinical assessment.